Short-Term Outcomes of Transcatheter Aortic Valve Replacement in Kidney Transplant Recipients: A Nationwide Representative Study. Issue 1 (2nd January 2021) - Hassanein, Mohamed; Abdelfattah, Omar M.; Saad, Anas M.; Isogai, Toshiaki; Gad, Mohamed M.; Ahuja, Keerat R.; Ahmed, Taha; Shekhar, Shashank; Fatica, Richard; Poggio, Emilio; Kapadia, Samir R.
ABSTRACT: Background : Kidney transplant is the preferred treatment for end-stage kidney disease due to a better quality of life and lower morbidity and mortality than dialysis. These patients are considered high-risk patients for surgical interventions. Transcatheter aortic valve replacement (TAVR) has been introduced as an alternative to surgical aortic valve replacement in patients at high operative risk with aortic stenosis (AS). However, the outcomes of TAVR in kidney transplant patients regarding benefits and harms have not been well-studied in nationally representative data. Methods : Patients hospitalized for TAVR between January 2012 and December 2017 were identified retrospectively in the Nationwide Readmissions Database (NRD). Patients were subdivided based on having a previous history of kidney transplant. Results : Our study included 171, 011 TAVR patients, of which 0.4% had a history of functioning kidney transplant. Patients with a history of kidney transplant generally had more rates of comorbidities and were more likely to develop in-hospital hemorrhagic stroke (0.7% vs. 0.1%, P = 0.004), ischemic stroke (4.5% vs. 2%, P < 0.001), acute kidney injury (25.3% vs. 13.4%, P < 0.001), and sepsis (3.9% vs. 1.6%, P < 0.001), but showed similar in-hospital mortality rates. These findings were confirmed after adjusting for other comorbidities. Conclusion : Patients with a history of kidney transplantation experience an increased risk of adverse outcomes following TAVR compared to non-kidney transplant patients. Further attention should be directed to measures to improve such outcomes in kidney transplant patients undergoing TAVR. Abbreviations: KT: kidney transplant; KTRs: kidney transplant recipients; TAVR: transcatheter aortic valve replacement; AS: aortic stenosis; SAVR: surgical aortic valve replacement; IHS: in-hospital stroke; AKI: acute kidney injury; ESKD: end-stage kidney disease; CKD: chronic kidney disease; TCEP: transcatheter cerebral embolic protection; DSCT: dual source computed tomography; VLCV: very low contrast volume